2016
DOI: 10.4238/gmr.15037641
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toll-like receptor 9 gene polymorphisms and risk of bacterial meningitis in a Chinese population

Abstract: ABSTRACT. We determined whether two common single nucleotide polymorphisms (SNPs) in the Toll-like receptor 9 gene (TLR9) (TLR9+2848 rs352140 and TLR9-1237 rs5743836) influenced susceptibility to bacterial meningitis in a Chinese population. The study comprised 126 patients with bacterial meningitis and 252 control subjects, all of whom were recruited from the Tuberculosis Hospital of Shanxi Province. Genotyping of TLR9+2848 rs352140 and TLR9-1237 rs5743836 was performed by polymerase chain reaction coupled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The prevalence of TLR-9 genotypes for C-1237T, C-1486T, and C+2848T polymorphisms in healthy controls was comparable with earlier reports in Chinese population. [8][9][10][11][12] The prevalence of homozygous mutant (TT) for TLR-9 C-1237T polymorphism was significantly higher when compared to other genotypes, which is in line with earlier studies. 10,11 The high prevalence of heterozygotes or homozygous mutant in various populations has been attributed to the local selection pressure of several infectious diseases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of TLR-9 genotypes for C-1237T, C-1486T, and C+2848T polymorphisms in healthy controls was comparable with earlier reports in Chinese population. [8][9][10][11][12] The prevalence of homozygous mutant (TT) for TLR-9 C-1237T polymorphism was significantly higher when compared to other genotypes, which is in line with earlier studies. 10,11 The high prevalence of heterozygotes or homozygous mutant in various populations has been attributed to the local selection pressure of several infectious diseases.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the prevalence of TLR-9 (C-1237T, C-1486T, and C+2848T) polymorphisms in healthy stomach was also not significantly different when compared to healthy controls of earlier published reports. 8,10,11 Interestingly, TLR-9 (C+2848T and C-1486T) mutants were more frequent in gastroduodenal ulcer patients compared to subjects with healthy stomach and healthy controls. These observations collectively suggest that TLR-9 polymorphisms possibly predispose subjects to development of gastroduodenal ulcer and related clinical complications.…”
Section: Discussionmentioning
confidence: 94%
“…Figure 1 shows the flow chart of meta-analysis search course. Based on the search strategy, four studies reporting seven groups of patients – three comprising both meningococcal (MM) and pneumococcal (PM) cases [9, 16, 17], and one reporting BM cases as a whole were identified [15] (Table 1). All but Wang's study used population-based controls.…”
Section: Resultsmentioning
confidence: 99%
“…TLR9 gene polymorphisms have also been associated with multiple diseases such as pulmonary tuberculosis, duodenal ulcers and altered cytokines in gastric mucosa, systemic lupus erythematosus and chronic obstructive pulmonary disease [10][11][12][13][14]. Of these polymorphisms, the rs352140 variant has been the one most investigated, and some have suggested that it is significantly associated with susceptibility to BM [15], but this has not been supported by other studies [9,16,17]. We therefore set out in this study to establish through a meta-analysis of published data whether TLR9 rs352140 polymorphism confers an increased risk for BM.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the rs352140 variant has been, however, associated with infections such as malaria and meningitis. [ 53 , 57 ] Specifically, the minor T allele has been associated with increased inflammation and thereby increased symptoms of these infectious diseases, possibly indicating a stronger immune reaction, as also noted in placental inflammation. [ 29 , 58 ] Whether or not such increased inflammatory response also protects from the development of breast cancer remains to be characterized.…”
Section: Discussionmentioning
confidence: 99%